Investigation of the Relationship Between Classroom Leadership Teaching Skills and Effective Communication Skills of Sport Sciences Faculty Students - Murat ATASOY; Meryem ALTUN EKİZ (ümit doğan üstün, 2022)
The aim of this study is to examine the relationship between the classroom leadership teaching skills and effective communication skills of sports sciences faculty students. In this study, the associational research model was used to examine the relationships. The population of the study consists of Kırşehir Ahi Evran University students, while the sample consists of 388 students, 172 female and 216 males, studying in different departments of the Faculty of Sports Sciences in the 2021-2022 academic year. In-class Effective Communication Skills Perception Scale developed by Gülbahar and Aksungur (2018) and In-Class Leadership Teaching Skills Perception Scale developed by Gülbahar (2017) were used as data collection tools. Since the data did not show a normal distribution, Mann-Whitney U Test, Kruskal-Wallis Test, Spearman's rho and descriptive statistics (%, n, min. Max. X, ss) were used. According to the research findings, while there was no significant difference in classroom leadership teaching skills perception scale scores according to gender and age, statistically significant difference was observed in classroom effective communication skills perception scale scores according to gender and age. Accordingly, the average rank of women was found to be higher than that of men, and the age range with the highest rank average is 26 years and over. According to the department variable; A significant difference was found between classroom leader teaching skills and classroom effective communication skills scores. Accordingly, the department with the highest rank average is sports management. According to the correlation result between classroom teacher leadership and effective communication in the classroom scores, it was found that there was a positive and significant relationship (r=.727, p<.01). Accordingly, it can be said that effective communication in the classroom will increase if the in-class teacher leadership skills of the sports sciences faculty students increase.